The role of Candida albicans in root caries biofilms: an RNA-seq analysis - EV, Laís Daniela (J Appl Oral Sci, 2020)
OBJECTIVE: This study sought to analyze the gene expression of Candida albicans in sound root surface and root caries lesions, exploring its role in root caries pathogenesis. METHODOLOGY: The differential gene expression of C. albicans and the specific genes related to cariogenic traits were studied in association with samples of biofilm collected from exposed sound root surface (SRS, n=10) and from biofilm and carious dentin of active root carious lesions (RC, n=9). The total microbial RNA was extracted, and the cDNA libraries were prepared and sequenced on the Illumina Hi-Seq2500. Unique reads were mapped to 163 oral microbial reference genomes including two chromosomes of C. albicans SC5314 (14,217 genes). The putative presence of C. albicans was estimated (sum of reads/total number of genes≥1) in each sample. Count data were normalized (using the DESeq method package) to analyze differential gene expression (using the DESeq2R package) applying the Benjamini-Hochberg correction (FDR<0.05). RESULTS: Two genes (CaO19.610, FDR=0.009; CaO19.2506, FDR=0.018) were up-regulated on SRS, and their functions are related to biofilm formation. Seven genes ( UTP20 , FDR=0.018; ITR1 , FDR=0.036; DHN6 , FDR=0.046; CaO19.7197 , FDR=0.046; CaO19.7838 , FDR=0.046; STT4 , FDR=0.046; GUT1 , FDR=0.046) were up-regulated on RC and their functions are related to metabolic activity, sugar transport, stress tolerance, invasion and pH regulation. The use of alternative carbon sources, including lactate, and the ability to form hypha may be a unique trait of C. albicans influencing biofilm virulence. CONCLUSIONS: C. albicans is metabolically active in SRS and RC biofilm, with different roles in health and disease.